Pursuing Truth : How Gender Shaped Catholic Education at the College of Notre Dame of Maryland - Oates, Mary J. (Book collections on Project MUSE., 2021)
"In Pursuing Truth, Mary Oates considers the history of the College of Notre Dame of Maryland (now Notre Dame of Maryland University), the first Catholic college in America to award the four-year baccalaureate degree to women. This book adds needed depth to the historiography of gendered higher education in the United States by exploring the struggle for equal access to Catholic higher education"--